592 Injured patients' interactions with health providers: implications for enhancing trauma care. (1st September 2016) - Braaf, Sandy; Ameratunga, Shanthi; Christie, Nicola; Cameron, Peter; Lyons, Ronan; Harrison, James; Ponsford, Jennie; Collie, Alex; Fitzgerald, Mark; Judson, Rodney; Nunn, Andrew; Attwood, David; et al.
Abstract : Background: The path to recovery following major trauma can involve a long trajectory of complex health care needs and multiple interactions with health professions. We explored the perspectives of seriously injured patients regarding issues that arise during their interactions with health providers. Methods: This qualitative study, nested within a population-based longitudinal cohort study, involved semi-structured telephone interviews conducted three years following injury with 64 adult major trauma patients purposively sampled from the Victorian State Trauma Registry. We report one aspect here. Thematic analysis was undertaken of interview transcripts. Results: The importance of effective communication was a theme that had implications in the in-hospital, rehabilitation and community care settings. Effective communication occurred when service providers conveyed detailed information in a sensitive and clear manner, frequently and actively involved patients in discussion, and were responsive to patients' questions. Such interactions encouraged information exchange and shared decision-making. Ineffective communication arose predominately during in-hospital care and at discharge from inpatient facilities. Themes related to hospital care included limited contact with health professionals, inability to process information, indirect communication, and struggling to deal with multiple health professionals. At hospital and rehabilitation discharge, themes included insufficient patient engagement, inadequate information flow and feeling disregarded. Ineffective communication resulted in discontinuity of care and preventable health problems. Conclusions: The communication and information needs of seriously injured patients were inconsistently met over the course of their recovery. The findings reveal the need for trauma care systems to support relevant training of service providers, engage patients in planning decisions, and provide information in appropriate forms.